FAMILY CAREGIVING ENVIRONMENT AND ENGAGEMENT IN ADVANCE CARE PLANNING. (11th November 2018) - Kim, K; Hong, M; Buckley, T
Abstract: This study examines the relationship between the family caregiving environment and older adults' engagement in advance care planning (ACP) which includes (1) informal talking about end of life care with someone and (2) formal engagement in ACP (i.e., having a durable power of attorney or having advance directive). Despite potential influences of family caregivers on engagement in ACP, limited studies have examined whether the family caregiving environment affects the care recipients' decision and choices in ACP. We combined two data sets: the 2012 National Health and Aging Trends Study (NHATS) and the 2011 National Study on Caregivers (NSOC; supplemental survey with caregivers of participants of the NHATS). A total of 328 cases who completed ACP questionnaires from the NHATS and whose caregiver completed the NSOC were included in our study. Logistical regression analyses showed that care recipients who were White and with a high school diploma were more likely to informally talk about ACP. Also, higher levels of disagreement between family members to care for older adults were associated with lower levels of formal engagement in ACP (OR=0.5); higher levels of caregiver burden with higher levels of formal engagement (OR=1.1). Age 85 or older, being White, high school diploma, fallen down last year were also related to higher levels of formal engagement in ACP. Results of this study indicate that the caregiving environment may differently affect care recipients' decisions regarding informal and formal engagement in ACP, suggesting different intervention strategies by types of ACP.